1993
DOI: 10.1192/bjp.162.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Morbidity in Survivors of Organised State Violence Including Torture

Abstract: The case notes documenting the psychological well-being of 100 survivors of torture and other forms of organised state violence were analysed retrospectively. The most common diagnoses were post-traumatic stress disorder (PTSD), major depression, and somatoform disorders. Of these, PTSD showed the strongest association with experience of torture. It is possible that PTSD has a dimensional nature, and that reactions to different stressors are heterogeneous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
2
3

Year Published

1994
1994
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(70 citation statements)
references
References 5 publications
5
60
2
3
Order By: Relevance
“…Our data confirm the expectations of other authors [6,4,7,13] that torture survivors suffer from post-traumatic sequels that most frequently fulfil the diagnostical criteria for PTSD. In the majority of our patients (n = 35), DSM diagnoses were not restricted to PTSD, but patients suffered from depressive disorders, anxiety disorders and from functional psychosis.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our data confirm the expectations of other authors [6,4,7,13] that torture survivors suffer from post-traumatic sequels that most frequently fulfil the diagnostical criteria for PTSD. In the majority of our patients (n = 35), DSM diagnoses were not restricted to PTSD, but patients suffered from depressive disorders, anxiety disorders and from functional psychosis.…”
Section: Discussionsupporting
confidence: 82%
“…The belief that only those sick or weak before an extreme experience will develop disorders after a traumatic event, which was a serious handicap for those surviving concentration camps after the Second World War [3] in regard to treatment and compensation, has been replaced by critical studies demonstrating serious and long-lasting sequels of physical and psychological violence [4][5][6][7]. The earlier model of a specific 'torture syndrome' has been abandoned by most authors [5], but it is yet by no means clear what disorders have to be seen as characteristic for torture sequels [8,9], a fact that could have important implications for treatment and rehabilitation of sequels to torture.…”
Section: Introductionmentioning
confidence: 99%
“…A case-note survey has broadly confirmed the presence of PTSD, major depression and somatoform symptoms (Ramsay, Gorst-Unsworth, & Turner, 1993). This study also indicated that different trauma types were associated with different PTSD patterns, although this had not been one of the prior predictions and little weight could therefore be attached to the finding.…”
mentioning
confidence: 50%
“…PTSD is common among prostituted women. In nine countries, Farley, Alvarez, Sezgin, Baral, Kiremire, Lynne, DuPlessis, DuPlessis, Gonzales, Spiwak, Cotton, and Zumbeck (in press) found that 68% met criteria for a diagnosis of PTSD, a prevalence comparable to battered women seeking shelter (Houskamp & Foy, 1991), rape survivors seeking treatment (Bownes, O'Gorman & Sayers, 1991), and survivors of state-sponsored torture (Ramsay,Gorst-Unsworth & Turner, 1993).…”
Section: The Invisibility Of Psychological Symptoms Among Women In Prmentioning
confidence: 99%